Importance of Hypervariable Region 2 for Stability and Affinity of a Shark Single-Domain Antibody Specific for Ebola Virus Nucleoprotein - Anderson, George P. (PLoS One, 2016)
Single-domain antibodies derived from the unique New Antigen Receptor found in sharks have numerous potential applications, ranging from diagnostic reagents to therapeutics. Shark-derived single-domain antibodies possess the same characteristic ability to refold after heat denaturation found in single-domain antibodies derived from camelid heavy-chain-only antibodies. Recently, two shark derived single-domain antibodies specific for the nucleoprotein of Ebola virus were described. Our evaluation confirmed their high affinity for the nucleoprotein, but found their melting temperatures to be low relative to most single-domain antibodies. Our first approach towards improving their stability was grafting antigen-binding regions (complementarity determining regions) of one of these single-domain antibodies onto a high melting temperature shark single-domain antibody. This resulted in two variants: one that displayed excellent affinity with a low melting temperature, while the other had poor affinity but a higher melting temperature. These new proteins, however, differed in only 3 amino acids within the complementarity determining region 2 sequence. In shark single-domain antibodies, the complementarity determining region 2 is often referred to as hypervariable region 2, as this segment of the antibody domain is truncated compared to the sequence in camelid single-domain antibodies and conventional heavy chain variable domains. To elucidate which of the three amino acids or combinations thereof were responsible for the affinity and stability we made the 6 double and single point mutants that covered the intermediates between these two clones. We found a single amino acid change that achieved a 10°C higher melting temperature while maintaining sub nM affinity. This research gives insights into the impact of the shark sdAb hypervariable 2 region on both stability and affinity.